2010
DOI: 10.1063/1.3280076
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic pumping optimization in microgrooved channels with ac electrothermal actuations

Abstract: An optimization methodology is developed and applied to an ac electrothermal pump design with patterned microgrooved features. The microgrooved configuration can overcome the restrictions of the conventional planar configuration on pumping performance by diminishing fast backward flows and suppressing prolonged streamlines. At all frequency excitations (0.2–1000 MHz) and ion concentration conditions (5×10−3–0.1 M), the optimum microgrooved configuration generates much faster flow rate than planar configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 22 publications
4
39
0
Order By: Relevance
“…5(a) and 5(b) show that there is no detectable velocity profile for fluidic channel depths Շ10 lm, which is in agreement with the parametric study carried out by Ref. 21. It seems that for this range of fluidic depths the flow would be observed if the order of magnitude of the size of electrodes was reduced correspondingly.…”
Section: A Effect Of Fluidic Channel Depthsupporting
confidence: 89%
See 3 more Smart Citations
“…5(a) and 5(b) show that there is no detectable velocity profile for fluidic channel depths Շ10 lm, which is in agreement with the parametric study carried out by Ref. 21. It seems that for this range of fluidic depths the flow would be observed if the order of magnitude of the size of electrodes was reduced correspondingly.…”
Section: A Effect Of Fluidic Channel Depthsupporting
confidence: 89%
“…Also, a parametric study performed by Ref. 21 showed that for asymmetric planar electrode configuration, increasing the depth to more than 500 lm, does not have a perceptible effect on mean velocity. In this section, MAET with two arrays of microelectrodes placed at the top and bottom of the microfluidic channel is compared to a conventional ACET micropump with a single microelectrode array at the bottom.…”
Section: A Thermal Aspectmentioning
confidence: 98%
See 2 more Smart Citations
“…The microgrooved structure increased the pumping capacity by five to six-fold as compared to a simple asymmetric electrode arrangement with the same effective dimensions. 30, 31 …”
Section: Microfluidic Operationsmentioning
confidence: 99%